Порівняльні дослідження процесів рідкого шлаковидалення при різних технологіях пилоподачі на пальники котла ТПП-210А - Kesova L.O.; Pobirovsky Yu.N.; Merenher P.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2017)
We present some results of studies of a TPP-210A boiler, burning ASh coal, under loads of the units of 200–300 MW at two technologies of dust feed to the burners: the traditional pneumatic dust transport with primary air and highly-concentration dust feed under pressure (PVKd) with estimating the influence of these technologies on the modes of liquid slag removal. The degree of influence of the main factors on the stability of liquid slag yield and the expenditure of fuel oil for lighting was determined.The results of studies have revealed the possibility of increasing the economical efficiency of boiler operation by reducing the fuel oil consumption for lighting with the use of PVKd technology, which should be considered as a method for improving furnace conditions in boilers, burning low-reaction coal at liquid slag removal.